2004
DOI: 10.1111/j.0022-1112.2004.00593.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environmental variables on fish feeding ecology: implications for the performance of baited fishing gear and stock assessment

Abstract: The effectiveness of baited fishing gear ultimately depends upon behaviour of the target speciesactivity rhythms, feeding motivation, and sensory and locomotory abilities. While any environmental parameter that mediates feeding or locomotion can have an important influence on the active space presented by the bait and fish catchability, few biologists have considered how such variation in behaviour might affect catch per unit effort (CPUE) and the resultant stock abundance estimates or population parameters. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
204
2
10

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(220 citation statements)
references
References 142 publications
(183 reference statements)
4
204
2
10
Order By: Relevance
“…Dickson 1993). Capture efficiency of baited gear is also influenced by fish behavior, which varies with temperature, light, current and fish density (Auster 1985, Stoner 2004. Although direct-count observations from submersibles have sometimes been used to estimate absolute densities of fish for comparison with traditional survey gear (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Dickson 1993). Capture efficiency of baited gear is also influenced by fish behavior, which varies with temperature, light, current and fish density (Auster 1985, Stoner 2004. Although direct-count observations from submersibles have sometimes been used to estimate absolute densities of fish for comparison with traditional survey gear (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…food availability (food quantity, in terms of TPM; food quality, in terms of POM and ƒ), temperature, DO level, etc. (Stoner 2004, Lall & Tibbetts 2009, Vanella et al 2012, Smith & Sanderson 2013. The relationship of SCR to TPM showed that food availability was the dominant factor affecting the feeding process of silver carp.…”
Section: Discussionmentioning
confidence: 98%
“…The effects of experience on grouping may have important implications for feeding and predator evasion as fish move into new environments during DVM or ontogenetic changes in habitat. Fishing operations may also be altered as the effectiveness of baited fishing gear is controlled in part by grouping behaviour (social facilitation) and temperature (Stoner 2004).…”
Section: Discussionmentioning
confidence: 99%